Heteronomy: poetic onthology without metaphysics - Balso, Judith; Vásquez T. , Carlos (Estudios de Filosofía, 2012)
Judith Balso develops in this piece an organic view of Fernando Pessoa’s Heteronomy. With it she aspires to show how Poetry faces, with its own recourses, the challenges and questions that belong to the realm of Ontology. So Pessoa is placed beyond the traditional separation between Philosophy and Poetry that pertains to Western Metaphysics. When one reads Pessoa one has to incarnate the creative writing of the poet to face the essential questions of being human: Existence, the question on Being and Nothingness, the relationship of Man with Nature, the Question on Language and through Language, the relationship of one Human Being with other Human Beings. So in his field are integrated a diversity of preocupations that range from Gnoseology to Aestetics, from Ethics to Literature, from the Thought on God to The Gods. Balso’s idea is that the crisis proper to Metaphysics finds in Pessoa not only and echo but even possible alternatives for renovation. Her essay invites one to establish a propositive relation lacking the prejudices of an opposition between Poetry and Philosophy.